PENGARUH KOMPETENSI, LINGKUNGAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KABUPATEN TOJO UNAUNA - Isnain, Moh. (Katalogis, 2013)
The objectives of this research are to know the effects of cempetency, work environment, and organizational commitment, simultaneously and partially on personnel’s performance at Educational, Youth and Sport Office in Tojo Unauna regency. This is survey method research using descriptive and verificative approach. Analysis tool used in this research is multiple linear regression. Population of this research covers all civil servants at Education, Youth and sport office in Tojo Unauna Regency with the number of 63 personnel, however only 58 that have been analyzed. The result show that constribution effect of competency, work environment, and organizational commitment on personnel’s performance is 23.2% (indicated by adjusted R square 0.232). this means that the contribution of three independent variables on personnel’s performance is 23.2% and 76.8% is affected by other factors for instance motivation, work culture and leadership style. Competency, work  environment, and organizational commitment simultaneously perform significant effects on personnel’s performance at education, youth and sport office in Tojo Unauna regency at the significant level of 0.001. partially, independent variables also perform sinificant effects on personnel’s performance where in competency significant at the  level of 0.049, work environment significant at the level of 0.042, and organizational commitment significant at the level of 0.036 respectively.